A case study on technology transfer process in Bhutan Telecom Limited - Tashi, Sonam; Islam, Nazrul; Ahmed, Kazi Mohiuddin; Shankar, Ravi; Bhutan Telecom Limited Thimphu, Bhutan (Pathum Thani, Thailand : Asian Institute of Technology, 2008)
Owing to market dynamics firms have to remain competitive to sustain in the ever changing market demands. Advancement in technology also provides opportunities to companies to explore new market. Technology can be either developed internally or can be bought from outside. The decision regarding whether to develop internally or buy is driven by several factors. Lack of resources hinders internal development of technology. Buying technology from outside also requires strategic assessment of technology, the vendors for the technology, motivations, and channel of transfer. Effectiveness of technology usually estimated by assessing the capabilities developed after the transfer process and extent of commercialization of technology in local market. Several enablers are identified in literature and tested for the impact they have in technology transfer like Availability of capital and Bhutan{u2019}s Technological development progress. Bhutan Telecom has been involved in technology transfer to build telecommunication infrastructure in Bhutan. ISM is a structured process that enables individuals or groups to develop a map of the complex relationships between the many elements involved in a complex situation. ISM is often used to provide fundamental understanding of complex situations, as well as to put together a course of action for solving a problem.
The research report submitted in partial fulfillment of the requirements for the degree of Master of Business Administration in Management of Technology
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2008
Keywords: Bhutan Telecom Limited; Technology transfer -- Bhutan